(untitled) (Global Journal of Science Frontier Research, 2020)
In this study, data related to the physical activities of the primary elementary school of the area, teaching methods, use of educational materials, library, toilets, teacher-student boundary wall etc were collect. Data were collected through direct interviews with the respondents in the light of the questionnaire. The results are presented by applying different statistical methods in processing and analyzing the data collected for the study. Data were collected separately from schools of different grades (A and B). As a result, there is an opportunity to analyze the data of government primary schools in different grades of grades separately. In order to carry out the research work, eight government primary schools were selected out of 16 schools in different char area of Gangachara Upazila under Rangpur district administrative areas. Of them, 4 were selected from Lohani char, 3 from Binabina char and 1 from Mutukpur char. The data were collected from selected 8 government primary school teacher were selected 16 primary teachers by using snowball sampling technique. The results showed that the physical infrastructure of the government primary schools in the char area is underprivileged. No separate modern facilities for girl students have been added to government primary schools in the char area. The required number of female teachers was not recruited in the government primary schools in the char area. Not all the combined efforts and initiatives of primary education of girl students were seen in the government primary schools of the Char region. The government primary schools in the Char region have not yet been converted into a sanctuary for female students, considering the overall aspect.